One-pot solution synthesis of carbon-coated silicon nanoparticles as an anode material for lithium-ion batteries. Issue 7 (2nd January 2020) - Wang, Fei; Song, Changsheng; Zhao, Baoxun; Sun, Lin; Du, Hongbin
Abstract : Carbon-coated silicon nanoparticles were synthesized via a one-pot solution method, delivering excellent performance in lithium ion batteries. Abstract : Carbon-coated silicon nanoparticles were in situ synthesized via a facile one-pot solution synthesis method, which delivered an excellent cycling performance with a retained discharge capacity of 1120 mA h g −1 and almost no capacity decay after 500 cycles at 2 A g −1 when evaluated as an anode material in lithium ion batteries.